PENGARUH MODEL DIRECT INSTRUCTION TERHADAP KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA TEMA 2 KELAS V - Elmi Ferisya Andriany; Riyadi Saputra (Dharmas Education Journal (DE_Journal), 2022)
This research is motivated by the low interest of students in learning Indonesian.  The low interest of students in learning Indonesian affects students' writing skills and students' inability to express ideas or ideas in written form.  The fact that we can see from the results of the Mid-Semester Assessment (MSA) is still unsatisfactory.  In this study, researchers conducted a study using the Direct Instruction model.  The purpose of this study was to determine the effect of the Direct Instruction model on writing skills in the Indonesian subject of theme 2 class V SD N 14 Koto Baru.  The type of this research is Pre-Experimental Design, the design of this research is One-Group Pretest-Posttest Design.  The research was conducted at SD N 14 Koto Baru.  The time of this research was carried out in the Even Semester of the 2020 2021 Academic Year. The sample in this study was class V totaling 35 students. Based on the results of the Wilcoxon signed rank test, a significance of 0.000 <0.05 was obtained.  So that the researcher can conclude that there is a fashion effect!  Direct Instruction on writing skills in Indonesian subjects theme 2 class v SDN 14 Koto Baru Based on research, that the Direct Instruction model has a good influence on students' writing skills in Indonesian subjects.